Studi Daya Dukung Tanah Lempung Lunak menggunakan Ecomix. - Setyanto, .; Putra, Andius Dasa; Permana, Erik (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
In this research, the soil to test is soft clay soil from Rawa Sragi area of Belimbing Sari village, inJabung sub district of East Lampung regency, Lampung province. The soil properties were as thefollowing: specific gravity 2.546; water content 50.64%, liquid limit 61.26%, plasticity limit30.77%, plasticity index 30.49%, and material sieve passing no. 200 was 90.42%. Additive mate-rial to use was Ecomix. There were three treatments of ecomix mixtures of 3 gr, 4 gr, and 5gr with0.4 kg cement and 6 kg soft clay soil samples. The mixture samples were letting aside for 7 daysand soaked for 4 days.The results showed that the ecomix addition to mixture or cement and soft clay soil was able toimprove the soil mechanical and physical properties. The physical test results such as specificgravity, optimal water content, and plasticity index tests showed decreasing results after soil sta -bilization. The maximum CBR value was obtained in mixture of 34.49% in non-soaked condition,while the lowest CBR value was 8.2% soaked condition. The CBR test results showed that the soilmixture of ecomix additive material and cement can be used for road construction subgrade be-cause the CBR value was â‰¥ 6%